AFFORDABILITY OF AFFORDABLE HOUSING IN NORTHERN REGION OF MALAYSIA (Malaysian Management Journal, 2023)
The problem of housing affordability has emerged as a significant concern in urban centers, particularly in emerging countries. Whileeach country defines affordability differently, housing affordability refers to the capacity to possess a residential property or dwellingthat satisfies fundamental living requirements in relation to its price, standard, and whereabouts. However, the majority of generallycomprised of individuals and families with lower to moderate incomes, residing in various urban areas across Malaysia find itdifficult to purchase a home. The aim of this research is to evaluate the housing affordability index in Malaysia’s Northern Region (Kedah, Pulau Pinang, Perak, and Perlis) by proposing a maximum affordable housing cost determined by income level. The findings revealed that the housing affordability index has deteriorated as a result of growing income-price inequalities. It is suggested that government or housing policy makers to be responsible to establish a fair housing price that is determined through convincing and widely accepted judgments. Establishing prices could be based on genuine supply and demand dynamics, rather than being influenced by unfair trading practices, manipulation, or exploitation.